2017
DOI: 10.1002/fam.2435
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of enhancing thermal protective clothing performance by incorporating aerogel and phase change materials

Abstract: Summary Thermal liners play a critical role in thermal protective performance for firefighter gear. Effective engineering of textile material is necessary to enhance this protective performance. A modified thermal protective erformance (TPP) tester was used to study the influence of incorporating aerogel and microencapsulated phase change materials (MPCMs) in thermal liners (including a traditional thermal liner, phase‐change layer, and aerogel layer) and the relevant parameters associated with enhanced therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Shaid et al 26 imbedded aerogels and PCMs in the thermal protective clothing to reduce the flammability of fabrics and improve the thermal protective performance. Zhang et al 27 selected two kinds of PCMs with different phase change temperatures (45°C and 50°C). The effects of the PCM and aerogel on the thermal protective performance were investigated under a medium intensity radiation of 15 kW/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Shaid et al 26 imbedded aerogels and PCMs in the thermal protective clothing to reduce the flammability of fabrics and improve the thermal protective performance. Zhang et al 27 selected two kinds of PCMs with different phase change temperatures (45°C and 50°C). The effects of the PCM and aerogel on the thermal protective performance were investigated under a medium intensity radiation of 15 kW/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, fillers with high thermal conductivity could be added, such as graphene, CNTs and metal nanoparticles [ 73 ] . Besides, since paraffin is not fire retardant, it should be encapsulated when applied in firefighting clothes 72 , 74 .…”
Section: Functional Materials and Structural Design For Improved Ppe Performancementioning
confidence: 99%
“…against liquid chemical agents), their thermophysiological properties may affect the user's safety. This complex issues are the subject of research [1,4,[14][15][16][17]. Houshyar et al [4] found that it is possible to improve the thermophysiological comfort properties of firefighters protective clothing by incorporation of superabsorbent fibres into the inner-layer fabric.…”
Section: Introductionmentioning
confidence: 99%
“…Rossi et al [16] analyzed the steam transfer through different types of textile layers in firefighter's clothing. Zhang et al [17] studied a critical role of thermal liners in thermal protective performance for firefighter gear. The work revealed positive impact of incorporating aerogel and microencapsulated phase change materials on protective properties of functional clothing.…”
Section: Introductionmentioning
confidence: 99%